2016
DOI: 10.4251/wjgo.v8.i8.583
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic pathways as a therapeutic target for colorectal cancer treatment

Abstract: Colorectal cancer is the second leading cause of death from cancer among adults. The disease begins as a benign adenomatous polyp, which develops into an advanced adenoma with high-grade dysplasia and then progresses to an invasive cancer. Appropriate apoptotic signaling is fundamentally important to preserve a healthy balance between cell death and cell survival and in maintaining genome integrity. Evasion of apoptotic pathway has been established as a prominent hallmark of several cancers. During colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 80 publications
2
69
0
Order By: Relevance
“…Apoptosis is the primary mechanism for the death of colorectal cancer cells induced by radiotherapy . In the course of radiotherapy, several apoptotic signaling pathways could be involved and the resistance to radiation may result from disruption of the pathways . In this study, RBBP6 inhibition obviously increased the extent of cell apoptosis after irradiation treatment, supporting an anti‐apoptotic function of RBBP6.…”
Section: Discussionsupporting
confidence: 65%
“…Apoptosis is the primary mechanism for the death of colorectal cancer cells induced by radiotherapy . In the course of radiotherapy, several apoptotic signaling pathways could be involved and the resistance to radiation may result from disruption of the pathways . In this study, RBBP6 inhibition obviously increased the extent of cell apoptosis after irradiation treatment, supporting an anti‐apoptotic function of RBBP6.…”
Section: Discussionsupporting
confidence: 65%
“…Appropriate apoptotic signaling is fundamentally important to preserve a healthy balance between cell death and cell survival and for maintaining genome integrity . In this study, we found that JQ1 and/or SAHA‐induced apoptosis can occur via both the intrinsic and extrinsic pathways.…”
Section: Discussionmentioning
confidence: 78%
“…Bcl2 and Bcl-xL inhibit apoptosis by preventing the release of cytochrome c from the mitochondria which leads to caspase activation and apoptosis [58]. Bcl-2 is more expressed in colorectal carcinoma than in ordinary mucosa and associated with CRC development [59,60]. Similarly, Bcl-xL is strongly up-regulated in human CRC specimens and has a driving role in CRC tumorigenesis and progression [61].…”
Section: Discussionmentioning
confidence: 99%